Penerapan Staffing untuk Meningkatkan Produktivitas Lembaga Pendidikan - Hesti Kusumaningrum; Faisal Ramadhito Alvinas; Mohamad Ilham Habibi; Muhammad Fikri Zhillalurahman (Pusat Riset dan Inovasi Nasional, 2024)
Proper staffing in educational institutions is a key factor in improving organizational productivity and efficiency. Employees' knowledge, skills and attitudes are key considerations in the staffing process. This article discusses the application of staffing to improve the performance of educational institutions, focusing on employee recruitment, training and development. The purpose of this study is to explore the importance of an effective recruitment approach, careful selection of human resources and targeted training in improving the quality of human resources. The results showed that proper staffing has a positive impact on organizational productivity and performance. In conclusion, good staffing requires careful planning, clear identification of needs, and ongoing support to ensure the long-term success of educational institutions.